Artificial Intelligence (AI) in Education: A Case Study on ChatGPT’s Influence on Student Learning Behaviors - Thuy Nhu Thi Nguyen , Nam Van Lai , Quyet Thi Nguyen (Educational Process: International Journal)
Background/purpose. The integration of ChatGPT at Ho Chi Minh City University of Technology and Education (HCMUTE) aims to transform teaching and learning dynamics. This research evaluates ChatGPT’s impact on student learning behaviors, exploring its potential to enhance educational outcomes while addressing ethical concerns.